Hubungan Faktor Meteorologis Dan Kepadatan Lalu Lintas Dengan Kualitas Udara Di Kota Tabanan - Hawatif Ruhil Millah; I Wayan Sudiadnyana; I Ketut Aryana; I Wayan Sali (Poltekkes Kemenkes Denpasar, 2022)
The main source of CO pollutants is transportation activities, especially motor vehicles. Air quality monitoring activities by monitoring systems will be carried out as an effort to control air quality. The purpose of this study was to determine the correlation between meteorological factors and traffic density with air quality in Tabanan City. The type of this research is an observational method with a cross-sectional study. The sampling technique is purposive sampling variations in 3 samples. The results obtained using the Pearson Product Moment correlation test, there are air temperature, humidity, and wind speed with air quality are 0.670, 0.497, and 0.398, while the traffic density with the air quality test get 0.000. These results indicate that air temperature, humidity, and wind speed have no significant correlation with air quality, and traffic density has a significant correlation with air quality. There is a need for socialization and promotion of using mass transportation like a bus to reduce CO pollutants and go green with emission-absorbing plants like Sansevieria sp. in Tabanan City.